Load Balancing Based on the Specific Offset of Handover - Liu Zhanjun; Ma Qichao; Ren Cong; Chen Qianbin (Institute of Advanced Engineering and Science, 2014)
Load Balancing technology in mobile wireless communication networks has been discussed largely. The current Load balancing algorithms have mainly adjusted the handover parameters without considering the inherent relationship of the handover parameters. In the paper, by considering the internal relationship of specific offset of handover, the constraint of the specific offser of handover was simplified, so the process of mobility load balancing algorithm was improved. With the improved mobile load balancing algorithm, the number of handover parameters was reduced and the signal process was simplified. Simulation results showed that the congestion rate was reduced, the resource utilization rate was improved and the Qos was improved.